Aspectos técnicos, econômicos e de sustentabilidade da produção de hidrogênio renovável - Braga, Gustavo Garcia Arantes [UNESP] (2015)
The development of power generation projects from renewable sources has increasingly highlighted in the energy scenario. In this aspect, Brazil has great potential for power generation coming from renewable sources, especially solar energy, wind energy and hydropower. Another source of energy in evidence is the hydrogen, since the use of this fuel does not cause the formation of gases causing the greenhouse effect. However, hydrogen can only be considered as a renewable source if its production occurs from other renewable sources. One form of hydrogen production is the electrolysis of water, this reaction consist in the process of water dissociation through the use of electrical energy. This work aims to characterize the production of hydrogen from electrolysis and expose the main technical, economic and environmental factors that influence the implementation of a central of hydrogen production. With regard to economic aspects, it was used the methodology proposed by Braga (2014), and graphs were presented in order to illustrate the cost of hydrogen production due to each of the sources studied. For environmental analysis, the AHP tool was used to a multiple criteria analysis as proposed by Saaty (1980), and it were associated the environmental aspects to economics. The results were satisfactory and suggest that the currently technologies employed are significantly more attractive when the economic aspects are analyzed, however according to the environmental aspects start to be considered, the renewable alternatives stand out